2023
DOI: 10.1029/2023gl103405
|View full text |Cite
|
Sign up to set email alerts
|

Regional Heatwave Prediction Using Graph Neural Network and Weather Station Data

Abstract: Heatwaves (HWs) lead to catastrophic consequences such as the mortality and morbidity of human (Xu et al., 2016), animal (Vitali et al., 2015, and crops (Brás et al., 2021), and severely deteriorate socioeconomic development. Furthermore, global climate change tends to increase the intensity, frequency, and duration of regional HWs (Clarke et al., 2022;Perkins-Kirkpatrick & Lewis, 2020), thus exacerbates the overall vulnerability of the natural environment and human society. In the past decades, studies have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Li et al. (2023) demonstrated the spatial interaction of observation stations in heatwave events. Other than spatial structure, GNNs can also be applied to represent the coupling of physical variables such as air‐sea interaction (e.g., Mu et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al. (2023) demonstrated the spatial interaction of observation stations in heatwave events. Other than spatial structure, GNNs can also be applied to represent the coupling of physical variables such as air‐sea interaction (e.g., Mu et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wu et al (2021Wu et al ( , 2022 utilized GNN to construct the spatial relation between rain gauges and forecast the rainfall in the East of China. Li et al (2023) demonstrated the spatial interaction of observation stations in heatwave events. Other than spatial structure, GNNs can also be applied to represent the coupling of physical variables such as air-sea interaction (e.g., Mu et al, 2021).…”
mentioning
confidence: 97%
“…GNN is a recent variant of deep learning algorithms and has a specialty in the modeling of unstructured data defined on graphs or networks (Scarselli et al, 2009). Its applications to climate science have covered a wide range of topics, including the predictions of global weather (Keisler, 2022;Lam et al, 2023), regional heatwaves (P. Li, Y. Yu, et al, 2023), air quality (S. Wang et al, 2020;Ejurothu et al, 2023;Ma et al, 2023), frost (Lira et al, 2022), and precipitation (Y. Chen et al, 2024), which demonstrates a high potential to tackle the complex urban environment with extensive geospatial datasets.…”
Section: Introductionmentioning
confidence: 99%